PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PROBLEM SOLVING PADA POKOK BAHASAN KESETIMBANGAN ION DAN pH LARUTAN PENYANGGA - Nur Atika; Abdullah Abdullah; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: The objective of this research was to develop the student’s activity paper on the subject of ionic equilibrium and ph of the buffer. The type of this research was reserach and development (R & D) with the 4-D development model which include Define, Design, Develop, and Disseminate. This research was to develop phase and be continue with a definite tryout. This research was conducted in FKIP Riau University. The object of this research was the students’ activity paper based on the problem solving. The data analysis technique used for this research was descriptive statistic descriptive. The descriptive analysis done by calculated the percentage of validation value. The average score of valuation to five expediency aspect of student’s activity sheet by validator’s team, such as the content properness, the criteria of problem solving, the language properness, course and the graphical has expediency value continued is 92%, 98%, 90, 90%, and 90%. Thus, the average score totality of student’s activity paper based on the problem solving subject of Ionic Equilibrium and pH of the Buffer is 92% which is in very valid criteria, means that the LKPD Developed is proper to be use. Whereas percentage response of teacher and student is 82,3% and 81% to LKPD with very practical and very interesting.Key Words: Student Activity Sheet, Problem Solving, and Ionic Equilibrium and pH of the Buffer.